Gender Dynamics in Minangkabau Customs: Women's Role in Safeguarding and Preserving High Heirlooms - Miswardi, Miswardi; Basir, Gusril; Rosman, Edi; Elfiani, Elfiani; Sanur Tarihoran, Adlan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study explores the gender dynamics within Minangkabau customs, focusing on the pivotal role of women in safeguarding and preserving high heirlooms (harta pusaka tinggi). As a matrilineal society, Minangkabau places women at the center of inheritance and cultural preservation, with high heirlooms serving as symbols of familial and communal identity. Using a qualitative approach, this research examines the responsibilities, challenges, and strategies employed by women in maintaining these assets. Data were collected through interviews with customary leaders, women inheritors, and community members, complemented by observations of traditional practices. The findings reveal that Minangkabau women hold a dual responsibility as custodians of both physical heirlooms, such as land and traditional objects, and intangible heritage, including customs and values. This role ensures the continuity of Minangkabau identity across generations. However, modernization, urbanization, and shifts in gender roles pose significant challenges to this tradition. Women often navigate complex negotiations between preserving traditional values and adapting to contemporary economic and social realities. The study highlights the adaptive strategies employed by women to balance these demands while safeguarding communal harmony. This research underscores the importance of empowering women in their roles as cultural custodians and the need for community-based initiatives to support the preservation of Minangkabau heritage. By illuminating the interplay between gender and cultural sustainability, this study contributes to broader discussions on matrilineal societies and the evolving role of women in cultural preservation.